Nietzsche and phenomenology : power, life, subjectivity - Daigle, Christine, 1967-; Boublil, Élodie (Studies in Continental thought., 2013)
What are the challenges that Nietzsche's philosophy poses for contemporary phenomenology? Elodie Boublil, Christine Daigle, and an international group of scholars take Nietzsche in new directions and shed light on the sources of phenomenological method in Nietzsche, echoes and influences of Nietzsche within modern phenomenology, and connections between Nietzsche, phenomenology, and ethics. Nietzsche and Phenomenology offers a historical and systematic reconsideration of the scope of Nietzsche's thought.